Exploration of Ethical Review Disputes and Regulatory Pathways of Off-label Drug Use - Xuelian TANG; Jue WU; Xiaoyan LI; Jiyin ZHOU (Yixue yu zhexue, 2025)
The ethical risks of off-label clinical use of drugs include many risks, incomplete laws and regulations, difficulties in risk-benefit assessment, and challenges in managing conflict of interest management and obtaining informed consent. There are no clear regulations in China that require ethics committees to review off-label drug use in clinical settings, and it is difficult to provide complete documents for ethics review for each off-label drug use case. There is a lack of standardized operating procedures and corresponding forms for the ethical review of off-label drug use. It is recommended that higher-level departments uniformly assess off-label drug use in clinical practice, rather than allowing ethics committees to arbitrarily expand their review scope. Healthcare institutions should strengthen supervision from an ethical perspective, which could serve as a supplement to the imperfect supervision of laws and regulations, further promoting the safe and standardized use of drugs.